How Is the Liberalization of Food Markets Progressing? Market Integration and Transaction Costs in Subsistence Economies - Zant, Wouter (2013)
The paper proposes a modification of Baulch's parity bounds model to measure the market integration of food markets in developing countries. Instead of extrapolating a single observation of transaction costs, it estimates transaction costs. Predicted transaction costs compare well with survey data of traders. Probabilities of market regimes, computed on the basis of predicted transaction costs, fluctuate significantly and do not support fixed regime probabilities over time. The probability of market integration with trade decreases consistently during food shortages, increasing either the probability of no trade or loss-making trade or the probability of profitable but unexploited trade opportunities. The data support a negative trend in market integration with trade.